2013
DOI: 10.5489/cuaj.221
|View full text |Cite
|
Sign up to set email alerts
|

Updated assessment of neoblader utilization and morbidity according to urinary diversion after radical cystectomy: A contemporary US-population-based cohort

Abstract: Background: In this paper, we examine contemporary utilization rates and determinants of neobladder (NB) after radical cystectomy (RC) relative to ileal conduit (IC), as well as provide an updated assessment of postoperative morbidity and mortality between NB and IC. Methods:Relying on the Nationwide Inpatient Sample (NIS), we abstracted patients who underwent RC between 2000 and 2010. Subsequently, NB and IC recipients were identified. Use of NB was assessed after accounting for case-mix. Propensity-based mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
2
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 24 publications
2
16
2
5
Order By: Relevance
“…And the morbidity and its related mortality were not statistically different between neobladder and ileal conduit similar to previous reports (P . 0.05, Table 2) (5,13,20,23). In addition, according to previous reports, no significant differences were observed in the overall Cxm rates of each urinary diversion, except that some predominant Cxms have been observed.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…And the morbidity and its related mortality were not statistically different between neobladder and ileal conduit similar to previous reports (P . 0.05, Table 2) (5,13,20,23). In addition, according to previous reports, no significant differences were observed in the overall Cxm rates of each urinary diversion, except that some predominant Cxms have been observed.…”
Section: Discussionmentioning
confidence: 50%
“…Therefore, the post-recovery was expected to be poorer and major Cxms were higher in IC, especially for the cerebrovascular/cardiovascular, infection-related Cxm and renal insufficiency, which were known to have a significant association with advancing age (13,26,28 -30,31). According to previous reports, some predominant complications have been observed and some major Cxm rates differed according to their diversion type (5,13,20,23). In the series of 493 cases of RC from Takashige et al, they reported fewer major Cxms and more infection-related Cxms of the Neo than the IC, whereas patients in the IC group had more wound-related complications (13).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Nach unserem Wissensstand ist die vorliegende Studie die erste Arbeit zu IC-Komplikationen, die konsequent eine standardisierte Klassifikation zur Erfassung von Komplikationen verwendet hat und alle IC-assoziierten Komplikationen aufführt, auch wenn sie als Frühkomplikation im postoperativen Intervall von 90 Tagen stattfanden [16]. Das IC ist die am häufigsten angewandte Harnableitung nach RC [5]. Dies könn-te zum einen in der größeren Verbreitung der operativen Expertise, ein IC anzulegen, oder aber auch in der meist kürze-ren Operationszeit im Vergleich zu kontinenten Harnableitungen begründet sein [14,18].…”
Section: Diskussionunclassified
“…Hierzu wird ein 15 bis 20 cm langes Ileumsegment ausgeschaltet, in das die Ureteren implantiert werden und welches abschließend mittels Stoma in der Regel im rechten Unterbauch ausgeleitet wird [3]. Obwohl insbesondere spezialisierte Zentren im Einklang mit den Empfehlungen internationaler Leitlinien bestrebt sind, RCKandidaten nach Möglichkeit eine kontinente Harnableitung anzubieten [4], ist die inkontinente Harnableitung mittels IC weiterhin das in der Gesamtheit am häu-figsten angewandte Verfahren [5].…”
unclassified